Proteção do patrimônio natural da Serra do Segredo (Caçapava do Sul, RS, Brasil): um diálogo entre a geoconservação e o Sistema Nacional de Unidades de Conservação (SNUC) - Silva, Elisângela Lopes da (2016)
Classical strategies of nature protection, in general, don t take into consideration the landscape s abiotic factors, that is, mineral, rocks, fossils, soil, hydraulic resources, which constitute the geodiversity of a given place. The majority of conservation units are created and delimited due to biotic factors in the area of interest and, in most cases, the abiotic elements are not considered or underrated in their creation. Being known and officially declared (State Common Law 14.708, July 15, 2015) as the Rio Grande do Sul s main city of geodiversity , Caçapava do Sul s administrative limits don t exhibit conservation units legally instituted to protect its geodiversity and biodiversity. In this context, this dissertation aims at defining and offering, based on a dialogue between geoconservation and SNUC, the typology and most adequate delimitation to protect the area named Serra do Segredo. This area possesses a unique geological and geomorphological setting, with singular ecosystems and organisms associated with these features. To achieve these goals, aspects related to the intrinsic geodiversity of Serra do Segredo were analyzed and places of bigger concentration, diversity and vulnerable population of vegetal species, mainly Parodia rudibuenekeri (Cactaceae), Petunia secreta (Solanaceae) e Pavonia secreta (Malvaceae), endemic to the landforms of Serra do Segredo, were identified. From these the possible legal frameworks were analyzed, within SNUC, to protect the natural patrimony (abiotic and biotic) of the region. Lastly, a geographic limit was proposed to delimitate a conservation unit for the place based on the biotic and abiotic features of Serra do Segredo.